The Satisfaction with Information about Medicines Scale (SIMS): a new measurement tool for audit and research. Issue 3 (1st September 2001) - Horne, R; Hankins, M; Jenkins, R
Abstract : Objective —To develop and examine the psychometric properties of the Satisfaction with Information about Medicines Scale (SIMS), a new 17-item tool designed to assess the extent to which patients feel they have received enough information about prescribed medicines. Methods —Patients from eight diagnostic categories were recruited at hospitals in London and Brighton and completed the SIMS questionnaire during hospital admission or attendance at outpatient clinic appointments. The SIMS was evaluated in terms of its ease of use, internal consistency, test-retest reliability, and criterion related validity using existing self-report measures of adherence and patient beliefs about medicines. Results —The SIMS was well accepted by patients in a variety of clinical settings and showed satisfactory internal consistency and test-retest reliability. As predicted, higher levels of satisfaction with medicines information were associated with higher levels of reported adherence, and lower levels of satisfaction were associated with stronger concerns about the potential adverse effects of medicines, providing evidence of criterion related validity. Conclusion —The SIMS performed well on a number of psychometric indicators and shows promise as a tool for audit (measuring patients' satisfaction with information about their prescribed medicines), research (evaluating current or new forms of information provision), and clinical practice (identifying the information needs of individual patients and as an aid to planning medicine related consultations).